PERBEDAAN PENENTUAN WAKTU IMSAK BULAN RAMADAN: Telaah Ijtihad Ilmiah Berdasarkan Ketinggian Fajar Shadiq - Maratus, Nuril Farida (Ahkam: Jurnal Hukum Islam, 2024)
The determination of imsak time during the month of Ramadan is crucial for Muslims in Indonesia, as it serves as a guideline for fasting. Imsak is a precautionary measure to ensure that sahur (pre-dawn meal) does not extend beyond its time and usually begins a few minutes before the Fajr (dawn) prayer. Differences in imsak schedules have been a point of contention, leading to confusion among the public. This research aims to analyze the variations in the determination of imsak time during Ramadan in Indonesia, with a focus on the standards for the height of the shadiq dawn. The article is composed, using library research methods by gathering relevant literature data. The research findings indicate that one of the main factors causing differences in imsak timing is the variance in the standards for the height of the shadiq dawn. This arises from differences in ijtihad (independent reasoning) regarding the sun's position at dawn between -20° and -18°. These different interpretations of the beginning of dawn affect imsak schedules, resulting in an approximately 8 minutes variation in imsak times across Indonesia.